Progress in the Pacific on sugar‐sweetened beverage taxes: a systematic review of policy changes from 2000 to 2019. (7th June 2021) - Teng, Andrea; Snowdon, Wendy; Win Tin, Si Thu; Genç, Murat; Na'ati, Elisiva; Puloka, Viliami; Signal, Louise; Wilson, Nick
Abstract: Objective : To systematically characterise sugar‐sweetened beverage (SSB) tax policy changes in Pacific Island countries and territories (PICTs) from 2000 to 2019. Methods : Medline, Google Scholar, Pacific Islands Legal Information Institute database, Factiva and news and government websites were systematically searched up to October 2019. Information was extracted on the date and SSB tax level change, tax type, included beverages, and earmarking; and checked for consistency with local experts. Results : Three‐quarters of PICTs had an SSB tax (n=16/21) and 11 of these were excise taxes that included both imported and locally produced beverages. The level of tax was over 20% in 14 jurisdictions. SSB tax was increased by more than 20 percentage points in eight PICTs. Most taxes were ad valorem or volumetric, three were earmarked and only two taxes targeted sugar‐sweetened fruit juices. The majority of countries (14/21) had different tax rates for imported and locally produced beverages. Conclusions : More than three‐quarters of PICTs have SSB taxes. More than one‐third increased these taxes since 2000 at an amount that is expected to reduce soft drink consumption. Implications for public health : Despite high‐quality tax design elements in some PICTs, SSB control policies could generally be strengthened to improve health benefits, e.g. by targeting all SSBs and earmarking revenue for health.